2019
DOI: 10.3390/v11110982
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Biological Characterization of a New Strawberry Cytorhabdovirus

Abstract: Virus diseases of strawberry present several complex problems. More than 25 viruses have been described in the genus Fragaria thus far. Here, we describe a novel rhabdovirus, tentatively named strawberry virus 1 (StrV-1), that infects F. ananassa and F. vesca plants. Genomic sequences of three distinct StrV-1 genotypes co-infecting a single F. ananassa host were obtained using combined Illumina and Ion Proton high-throughput sequencing. StrV-1 was transmitted to herbaceous plants via Aphis fabae and A. ruborum… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 46 publications
1
34
0
Order By: Relevance
“…To further investigate the phylogenetic relationship of cytorhabdoviruses, we aligned 28 RdRP amino acid sequences (2374 aa in length, including gaps) from reference cytorhabdoviruses available in Genbank, including two sequences derived from transcriptomes of B. tabaci ( Table S2 ). The phylogenetic analysis shows that cytorhabdoviruses cluster in monophyletic groups according to its potential vector: aphid [ 35 , 36 , 37 , 38 , 39 ], planthopper [ 40 , 41 , 42 , 43 , 44 , 45 ], leafhopper [ 46 ], whitefly, and an undescribed vector ( Figure 6 ). As previously suggested [ 7 , 47 , 48 ], BaCV isolates and PpVE were closely related to B. tabaci TSA 2 (AKC57270.1), confirming that these viruses belong to the species Papaya cytorhabdovirus .…”
Section: Resultsmentioning
confidence: 99%
“…To further investigate the phylogenetic relationship of cytorhabdoviruses, we aligned 28 RdRP amino acid sequences (2374 aa in length, including gaps) from reference cytorhabdoviruses available in Genbank, including two sequences derived from transcriptomes of B. tabaci ( Table S2 ). The phylogenetic analysis shows that cytorhabdoviruses cluster in monophyletic groups according to its potential vector: aphid [ 35 , 36 , 37 , 38 , 39 ], planthopper [ 40 , 41 , 42 , 43 , 44 , 45 ], leafhopper [ 46 ], whitefly, and an undescribed vector ( Figure 6 ). As previously suggested [ 7 , 47 , 48 ], BaCV isolates and PpVE were closely related to B. tabaci TSA 2 (AKC57270.1), confirming that these viruses belong to the species Papaya cytorhabdovirus .…”
Section: Resultsmentioning
confidence: 99%
“…Rujana hosted five different viruses: strawberry crinkle virus (SCV; family Rhabdoviridae ; genus Cytorhabdovirus ; two genotypes), strawberry virus 1 (StrV-1; family Rhabdoviridae ; genus Cytorhabdovirus ; two genotypes), strawberry polerovirus 1 (SPV1; family Tombusviridae , genus Luteovirus ), strawberry mottle virus (SMoV; family Secoviridae ; genus Stramovirus ), and olive latent virus 1 (OLV-1; family Tombusviridae ; genus Alphanecrovirus ). The 1/2017 isolates of StrV-1 and SPV1 were described earlier [ 12 , 13 ]. Furthermore, several contigs that resembled umbraviruses were obtained.…”
Section: Resultsmentioning
confidence: 99%
“…Such high divergence of genomic sequences is not unique among viruses infecting strawberry plants. For example, three variants of a rhabdovirus StrV-1 coinfecting the same plant shared 76–87% of nt identity in their genomes [ 12 ]. At the same time, the strawberry plant was hosting three RNA1 and three RNA2 variants of a stramovirus, SMoV (GenBank accession numbers MH013322-7).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The severity of symptoms varies, and plants may also be symptomless. The virus was detected in 31% of strawberry field samples in the Czech Republic (Fránová et al, 2019). He et al (2021) found an infection rate of about 10% in samples from China, Shandong province, indicating that it may pose a potential threat to global strawberry production; however, information about its harmfulness is lacking.…”
Section: Introductionmentioning
confidence: 99%